Disclosing the 'Big C': What Does Cancer Survivorship Signal to Employers? - Philippe Sterkens; Adelina Sharipova; Stijn Baert (Institute of Labor Economics (IZA), 2022)
To study hiring discrimination against cancer survivors, we conduct a vignette experiment in which American and British recruiters evaluate fictitious job candidates. Candidates differed by periods of non-employment in their career, including non-employment due to suffering from cancer. We study the effect of cancer experiences on the recruiters' hiring decisions, as well as its effect on underlying candidate perceptions, related to various potential forms of stigma identified in the literature. We find that employment opportunities are lower for candidates with a history of cancer, compared to candidates without such a gap. This penalty is particularly explained by perceptions that these candidates will have higher sick leave probabilities and create additional costs. However, relative to candidates with a comparable gap due to depression or personal reasons, former cancer patients are less stigmatised, with relatively favourable assessments of their emotional abilities, social abilities, motivation and positive impact on workplace culture.
Keywords: I10; I12; J70; J71; 330; hiring discrimination; cancer; depression; signalling